Intestinal Obstruction due to Bezoar in Elderly Patients: Risk Factors and Treatment Results. (17th February 2019) - Altintoprak, Fatih; Gemici, Eyup; Yildiz, Yasin Alper; Yener Uzunoglu, Mustafa; Kivilcim, Taner
Abstract : Purpose . Bezoars are foreign particles from the accumulation of indigestible materials in the gastrointestinal system and a rare cause of mechanical intestinal obstruction. We aimed at investigating differences in risk factors for the development of intestinal obstruction associated with bezoar in elderly patients. Methods . Hospital records of patients who underwent surgery associated with phytobezoar between January 2004 and May 2016 were retrospectively evaluated. Patients were divided into two groups [<65 years (Group 1) and ≥65 years (Group 2)]. Data were examined regarding presence of comorbidity, history of abdominal surgery, operation time, bezoar site, surgical technique, length of hospitalization, morbidity, and mortality. Results . Of 121 patients enrolled, 48 (39.7%) were male and 73 (60.3%) were female (range: 24-86 years). Group 1 consisted of 69 patients aged < 65, while Group 2 consisted of 52 patients aged ≥ 65. Comorbidity was reported in 52 (42.9%) patients (mostly diabetes mellitus, 20.7%), while 60 patients (49.6%) had history of abdominal surgery (mostly peptic ulcer, 27.3%). No statistical differences were found between the two groups in terms of sex, bezoar site, surgical technique preferred, history of abdominal surgical intervention, pre- and postoperative CT examination, morbidity rates, and length of hospitalization. But, ratio of peptic ulcer operations history, presence of total comorbidity, and time of surgery decision was higher in Group 2 patients. Conclusion . In bezoar-related intestinal obstruction, duration and outcome of treatment are not affected by age distribution. Possibility of bezoar should primarily be considered in elderly patients with history of peptic ulcer operation.